Situaciones jurídicas donde se extiende la estabilidad laboral reforzada al padre de familia (2022)
At present in our country and in different parts of the world we are experiencing situations of change in work and family roles between men and women who, due to different circumstances, are presenting the figure of the father who is the head of the family, who was helpless and unequal in the face of the woman, because in Colombia the regulations only emphasized the protection of women in a state of pregnancy and after their birth, which is why the high courts decided to carry out an analysis and it was found that when the father is the one who has the reins of the home, either because his partner died, because he left home or that in the case of being present he was in charge and caring for disabled minor children, he was not protected by a legal figure against his employer that would provide job stability reinforced by the jurisdiction of paternity and those of his family core. That is why, taking into account ILO Convention 156 issued in 1981, which refers to equal opportunities and treatment between workers and workers, the high courts of our country proceeded to set a jurisprudential precedent guaranteeing the right to equality, the vital minimum, work and a dignified life, protecting the essential nucleus of society, which is the family, regardless of whether the person in charge was a man or a woman. In this order of ideas, the jurisprudential precedent requires the Congress of the Republic to proceed to legislate in favor of the father of a family who, with the fulfillment of certain requirements, is guaranteed his right to reinforced labor stability, having today the Law 2141 of the year 2021, will modify articles 239 and 240 of the Substantive Labor Code, in order to establish the Paternity Jurisdiction and Law 2114 of the same year 2021, through which paternity leave is extended.